DIMENSI LIBERAL DALAM PEMIKIRAN HUKUM IMAM ASY-SYAUKANI - Ahmad Tubagus Surur (Jurnal Hukum Islam, 2010)
In the realm of liberals, ethic and justice values are regarded as the qath'i and eternal values that need upholding at the longest, while the rest is just particular and technical matter. Liberal schools has more intention on the sociological context rather than textual approach. So restriction on performing ijtihad is undoubtedly unintended; otherwise having wider space for ijtihad is absolutely required. This paper tries to uncover some dimensions of asy-Syaukani legal thought which is regarded as a liberal schools.